2020
DOI: 10.15575/jtk.v5i1.7971
|View full text |Cite
|
Sign up to set email alerts
|

Analysis the 21st Century Skills of Students in Chemical Equilibrium Learning With Flipped Classroom-Collaborative Problem Solving Model

Abstract: This study aimed to analyze the 21st century skills of students in learning chemical equilibrium with the Flipped Classroom-Collaborative Problem Solving model. Flipped Classroom is a learning model that students learn first outside the classroom through video, then carry out active activities in class such as discussions, presentations, making posters, and doing practicum. Collaborative problem solving is done when students discuss in solving problems for each learning activity. The research method us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 18 publications
2
2
0
1
Order By: Relevance
“…Through the active engagement, pre-service teachers in the experimental class developed more conceptual understanding and developed thinking skills that enabled them to move beyond understanding to knowledge application and synthesis. The finding is similar to previous studies that find FIBL could promote creativity, critical thinking and problem-solving skills in chemistry (Karyadi et al, 2020;Paristiowati et al, 2019). It can be concluded that flipped classroom and inquiry-based learning are effective learning approaches that enhance knowledge development of new skills that facilitate learning real-life problems.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Through the active engagement, pre-service teachers in the experimental class developed more conceptual understanding and developed thinking skills that enabled them to move beyond understanding to knowledge application and synthesis. The finding is similar to previous studies that find FIBL could promote creativity, critical thinking and problem-solving skills in chemistry (Karyadi et al, 2020;Paristiowati et al, 2019). It can be concluded that flipped classroom and inquiry-based learning are effective learning approaches that enhance knowledge development of new skills that facilitate learning real-life problems.…”
Section: Discussionsupporting
confidence: 88%
“…The analysis of the results showed the learning model enabled students to become independent, active learners. The authors concluded that the model enhance students' collaborative, communication, creativity, and critical thinking skills (Karyadi et al, 2020).…”
Section: Effects Of a Flipped Inquiry-based Classroom On Chemistry St...mentioning
confidence: 99%
“…Project-based learning itself has been proven to be effective in improving students' communication skills, such as the study of Asih et al (2019) which showed project-based learning enhanced communication skills of vocational students. This was in line with the Karyadi et al (2020) research which showed that communication skills were developed using PjBL. The study by (Haatainen & Aksela, 2021) found that 21 st century skills could be developed using PjBL.…”
Section: Communication Communicationsupporting
confidence: 88%
“…During the process of discussing the problems contained in the worksheet, students can develop ideas and ask questions that can improve critical thinking skills (Karyadi et al, 2020) .The process of identifying and understanding problems can lead to learners for critical thinking (Mahanal et al, 2019).…”
Section: Jurnal Tadrismentioning
confidence: 99%